Ebola Preparedness Planning and Collaboration by Two Health Systems in Wisconsin, September to December 2014. (15th September 2015) - Leonhardt, Kathryn Kraft; Keuler, Megan; Safdar, Nasia; Hunter, Paul
Abstract: We describe the collaborative approach used by 2 health systems in Wisconsin to plan and prepare for the threat of Ebola virus disease. This was a descriptive study of the preparedness planning, infection prevention, and collaboration with public health agencies undertaken by 2 health systems in Wisconsin between September and December 2014. The preparedness approach used by the 2 health systems relied successfully on their robust infrastructure for planning and infection prevention. In the setting of rapidly evolving guidance and unprecedented fear regarding Ebola, the 2 health systems enhanced their response through collaboration and coordination with each other and government public health agencies. Key lessons learned included the importance of a rigorous planning process, robust infection prevention practices, and coalitions between public and private health sectors. The potential threat of Ebola virus disease stimulated emergency preparedness in which acute care facilities played a leading role in the public health response. Leveraging the existing expertise of health systems is essential when faced with emerging infectious diseases. ( Disaster Med Public Health Preparedness . 2016;10:691–697)